2023
DOI: 10.3389/fnagi.2023.1068943
|View full text |Cite
|
Sign up to set email alerts
|

Cortical activation and functional connectivity during locomotion tasks in Parkinson’s disease with freezing of gait

Abstract: BackgroundFreezing of gait (FoG) is a severely disabling symptom in Parkinson’s disease (PD). The cortical mechanisms underlying FoG during locomotion tasks have rarely been investigated.ObjectivesWe aimed to compare the cerebral haemodynamic response during FoG-prone locomotion tasks in patients with PD and FoG (PD-FoG), patients with PD but without FoG (PD-nFoG), and healthy controls (HCs).MethodsTwelve PD-FoG patients, 10 PD-nFoG patients, and 12 HCs were included in the study. Locomotion tasks included nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…The increased premotor area activity in the PD group during turning and doorway passage is in line with previous fMRI studies 44,45,78 and one previous fNIRS study. 79 Even while there were differences between the fMRI studies' findings of increased or decreased activity, they all identified the SMA as a significant locus of action. The fNIRS study reported increased SMA and PMC activity during turning in people with PD compared to controls, but not in freezers.…”
Section: The Premotor Areas Are Consistently Related To Freezing Path...mentioning
confidence: 93%
See 1 more Smart Citation
“…The increased premotor area activity in the PD group during turning and doorway passage is in line with previous fMRI studies 44,45,78 and one previous fNIRS study. 79 Even while there were differences between the fMRI studies' findings of increased or decreased activity, they all identified the SMA as a significant locus of action. The fNIRS study reported increased SMA and PMC activity during turning in people with PD compared to controls, but not in freezers.…”
Section: The Premotor Areas Are Consistently Related To Freezing Path...mentioning
confidence: 93%
“…The fNIRS study reported increased SMA and PMC activity during turning in people with PD compared to controls, but not in freezers. 79 However, this study did not specify whether freezing episodes were excluded from analysis.…”
Section: The Premotor Areas Are Consistently Related To Freezing Path...mentioning
confidence: 97%
“…Its robust resistance to motion artifacts, coupled with superior temporal resolution compared to functional magnetic resonance imaging (fMRI) and better spatial resolution relative to electroencephalogram (EEG), positions fNIRS as a promising tool, particularly in identifying early cognitive impairments in PD patients (Oku and Sato, 2021;Pereira et al, 2023;Su et al, 2023). Current studies utilizing fNIRS have identified differences in frontal cortex activation in PD patients during motor tasks compared to healthy subjects (Feng et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other brain functional imaging techniques, fNIRS has the following advantages: high temporal resolution (~10 Hz), good spatial resolution (2-3 cm), being non-invasive or non-traumatic, real-time monitoring, easy continuous and repeated measurement, low cost, miniaturization, portability, anti-motion artifacts, suitable for a wider range of individuals, and easy to combine with other techniques for multimodal functional imaging, including functional magnetic resonance imaging (fMRI), positron emission tomography (PET), magnetoencephalography (MEG), electroencephalography (EEG), event-related potential (ERP), or electromyography (EMG) (33,(35)(36)(37). fNIRS experiments can be carried out in the natural environment without constraints and large amplitude movement monitoring (38). Thus, given its technical properties, especially the anti-motor artifact property, fNIRS has merged as an ideal brain functional imaging techniques for detecting MNS activation.…”
Section: Introductionmentioning
confidence: 99%